2001
DOI: 10.1034/j.1600-0412.2001.801109.x
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic pain during pregnancy is associated with asymmetric laxity of the sacroiliac joints

Abstract: Increased SIJ laxity is not associated with PRPP. In fact, pregnant women with moderate or severe pelvic pain have the same laxity in the SIJs as pregnant women with no or mild pain. However, a clear relation between asymmetric laxity of the SIJs and PRPP is found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(80 citation statements)
references
References 27 publications
(51 reference statements)
1
72
0
7
Order By: Relevance
“…It is a valid and reliable tool to assess the ability to transfer load between the spine and the legs via the pelvis. 42,50,51 Several studies demonstrated its usefulness as a screen for core muscles. 52 -56 Other studies analyzed this test in carefully selected subgroups of subjects, such as patients with sacroiliac joint pain 57 or with posterior pelvic pain since pregnancy.…”
Section: Clinical Tests-overview On Diagnostic Accuracymentioning
confidence: 99%
“…It is a valid and reliable tool to assess the ability to transfer load between the spine and the legs via the pelvis. 42,50,51 Several studies demonstrated its usefulness as a screen for core muscles. 52 -56 Other studies analyzed this test in carefully selected subgroups of subjects, such as patients with sacroiliac joint pain 57 or with posterior pelvic pain since pregnancy.…”
Section: Clinical Tests-overview On Diagnostic Accuracymentioning
confidence: 99%
“…Putatively, the unilateral innominate movement pattern is indicative of a particular model of physiological restriction, which derives from an asymmetric stiffness between the pelvic joints in SIJ-positive individuals. 2.1 ± 1.6 1.9 ± 1.8 1.7 ± 1.5 1.5 ± 1.2 Sagittal innominate range of motion (degrees) (Mean ± SD) Right 2.8 ± 2.6 3.2 ± 2.2 4.5 ± 4.6 2.5 ± 2.6 Left 3.5 ± 2.1 3.7 ± 2.3 3.6 ± 3.0 2.9 ± 2.0 Asymmetric stiffness has been demonstrated previously in patients experiencing pregnancy related pelvic girdle pain (Damen et al, 2001(Damen et al, , 2002. Moreover, Bussey and Milosavljevic (2013), also found a similar unilateral pattern in AS participants.…”
Section: Discussionmentioning
confidence: 83%
“…Disability as the result of pain is often measured using the Quebec Back Pain Disability Scale. While this scale is used primarily to measure disability from nondescript low back pain not related to pregnancy, it can be adapted to use for pregnancy-related pain [21][22][23]. Several studies have attempted to develop a system to evaluate the extent and effect of pain specifically during and after pregnancy.…”
Section: Diagnosismentioning
confidence: 99%